Ortus medicin{uE809}d est, Initia physic{u0A6E}avdita : Progressus medicin{u0BAF}vus, in Morborum Ultionem, ad Vitam Longam - Helmont, Jean Baptiste van, 1577-1644.; Helmont, Franciscus Mercurius van, 1614-1699 ([Netherlands] : Elsevier, 2014)
Jan Baptist van Helmont (1580-1644) was educated at Louvain, and could not make up his mind as to which science to pursue professionally. He eventually chose to become a physician, but continued experimenting in other fields. Van Helmont is generally considered the father of pneumatic chemistry, and was the first to discover that there are gases distinct from atmospheric air. Van Helmont even claimed that the word'gas' was his own invention. After his death in 1644, his son edited his collected works. Under the title The Origin of Medicine, they were published by the Elzevier family in Amsterdam in 1648.
'First published by Louis Elzevier in 1652. Republished by Elsevier B.V. in 2014.'
Online resource; title from PDF title page (ScienceDirect, viewed March 30, 2015).
Elsevier
Keywords: Medicine -- Early works to 1800.; Medicine; Electronic books; Early works